Factors Affecting Farmers' Capacity in Handling Harvest and Post-Harvest Mango Export Commodities Gedong Gincu - Ade Liyani; Aisyah Nur Rahmah; Muhamad Adib Ramdan; Muhamad Abdur Gofar Fazri; Dodi Budirokhman; Wachdijono Wachdijono (Pusat Publikasi Nusantara, 2023)
The aims of this study were (1) to determine the effect of stakeholder roles and direct access to information on farmer capacity in harvest and postharvest handling, and (2) to determine the influence of the role of stakeholders and access to information on the capacity of farmers in handling harvest and postharvest through. The research was conducted in Majalengka Regency with the central areas of Majalengka District and Panyingkiran District. The time of the research was carried out in August 2023. The determination of the sample was carried out by census on 30 farmers who had supplied gedong gincu mangoes to exporters. Data analysis used path analysis with the independent variable the role of stakeholders and access to information with the dependent variable being the farmer's capacity in handling harvest and postharvest through farmer behavior. data analysis using path analysis. The results of the analysis show that there is an influence on the role of stakeholders and access to information on the variable capacity of farmers in handling harvest and postharvest directly or through farmer behavior. The first path equation is Y = 0.391 + 0.517 + 0.796 and the second path equation is Y = 0.336 + 0.420 + 0.445 + 0.630. The effect of stakeholder roles on farmer capacity directly or indirectly is 0.500, the effect of information access on farmer capacity is 0.662 and the influence of farmer behavior on farmer capacity is 0.420